Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling

Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Computational investigation on the catalytic activity of Rh-6 and Rh4Ru2 clusters towards methanol activation - Ghatak, Kamalika; Sengupta, Turbasu; Krishnamurty, Sailaja; Pal, Sourav (Theoretical Chemistry Accounts, 2014)
Catalysis of molecular activation of small molecules through scission of strong chemical bonds is one of the major challenges faced by chemists. More specifically, activation of the strong C-H and O-H bonds of various alcohols, especially methanol, is one of the various important intermediate steps of key organic reactions. Our present work explores a suitable metal cluster catalyst towards methanol dissociation. In particular, we have examined the effect of ruthenium doping (Rh:Ru = 2:1) on the catalytic activity of Rh-6 cluster towards methanol dissociation. Density functional theory-based calculations illustrate two competitive pathways for methanol dissociation, which are via O-H and C-H bond breaking. Both the pathways are found to be energetically favourable in the presence of bimetallic and mono-metallic clusters. Importantly, energy barrier for O-H bond dissociation reduces considerably in doped cluster as compared to pure Rh-6 cluster and is smaller than the values reported for a number of other small metallic clusters.
Keywords: Bimetallic Clusters; Density Functional Theory (DFT); Doping; Methanol Activation; Rhodium Clusters

Enhanced mineralization of gaseous organic pollutant by photo-oxidation using Au-Doped TiO2/MCM-41 - Tangale, Nilesh P.; Belhekar, Anuja A.; Kale, Kishor B.; Awate, Shobhana V. (Water Air and Soil Pollution, 2014)
The synthesis, characterization, and photocatalytic evaluation of titania-loaded MCM-41 with and without Au doping are reported in the present study. The samples were characterized by powder XRD, TEM, low temperature N-2 adsorption/desorption, UV-Vis, and FTIR. UV-induced vapor-phase photo-oxidation of acetone was used as a probe reaction to study the role of Au in mineralization of volatile organic compounds (VOCs), viz. acetone at different concentrations. The doping of Au in titania-loaded MCM-41 resulted in the decrease of BET surface area, total pore volume, and average pore size. UV-Vis diffuse reflectance spectra of Au-doped titania-loaded MCM-41 showed the red shift in their absorption bands compared to titania-loaded MCM-41. The activity of mineralization of acetone by photocatalysis for 2 % Au-doped titania-loaded MCM-41 was found to be similar to 1.6 times higher than titania-loaded MCM-41. The presence of cocatalytic nanosized gold might be responsible for their enhanced activity on account of the delayed recombination of electron/hole pair. Although, almost complete mineralization of acetone was observed irrespective of the initial concentration of acetone in air (up to 3.72 mol%) by all the catalysts, 2 wt.% Au-doped titania-loaded MCM-41 has shown the most enhanced activity.
Keywords: Acetone; Doping; Gold; Mineralization of VOCs; Photo-oxidation; TiO2/MCM-41

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis

Nanocellulose-doped superabsorbent polymer for improved absorption properties in sanitary pad applications - Mandava, Srimukhi; Nagar, Harsha; Kumar, D. B. Rohini; Aniya, Vineet (International Journal of Biological Macromolecules, 2025)
An important disposable hygienic absorbent is the female sanitary napkin wherein superabsorbent polymers (SAP) are incorporated into it to increase the absorption capacity. Nevertheless, it has been discovered that SAPs have negative consequences on the environment and the user's health. The present study explores doping nanocellulose, into an acrylic acid-based SAP matrix to enhance absorption performance, leveraging nanocellulose's high surface area and hydrophilicity. Different SAP-nanocellulose compositions were tested, and characterizations like Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FT-IR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) confirmed the successful incorporation of nanocellulose into the SAP structure. Performance tests showed enhanced absorption properties in SAPs doped with nanocellulose compared to unmodified SAPs. The 70-30 composition significantly outperformed unmodified SAP (100-0). Free absorbency was highest for unmodified SAP, while 70-30 almost equaled in equilibrium absorbency in distilled water, but excelled in saline, simulated, and animal blood. Schott's pseudo-second-order model and Fickian diffusion were used to identify the kinetic swelling of SAP. For absorption under load, 70-30 attained 28.7 g/g in saline, a 28.91 % increase over unmodified SAP. In CRC, 70-30 exceeded unmodified SAP by 37 % in saline and 53 % in simulated blood demonstrating enhanced stability and absorbency.
Keywords: Absorption properties; Animal blood; Doping; Nanocellulose; Sanitary pads; Superabsorbent polymer